PENGARUH INJEKSI UAP AIR TERHADAP KUALITAS EMISI PADASUZUKI SMASH 110 - , ANANTA WIKRAMA, Ir. Fx.Sukidjo, MT. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The use of motor vehicle should be followed by protection against damages on the environment, since the exhaust gas from combustion engine has significantly affect on air and environmental pollutants. As we know that the process of fuel combustion from flue gas produces a theoretically contain elements of CO, COcor, CO2 and HC, that are polluting the environment in the form of air pollution. And 70% of air pollution produced by motor vehicles. Therefore we need a technology that can reduce pollution from exhaust emissions. And we try to give an unbiased solution to overcome the problem of air pollution by using steam injection, steam injection is a system that injects water vapor into the combustion chamber in order to increase the oxygen and hydrogen in the combustion chamber, reducing the mass of fuel within the combustion chamber and improve burning. So in present study, performed experiments on single-cylinder otto engine steam injected in the intake manifold, and see to what extent the effect of water vapor on the performance of the machine. The study was conducted with variation engine rpm, and the rate of water vapor. Where the rate of water variation by using valves, and the characteristics of the visits is the fuel consumption and exhaust gas analysis. The result is quite satisfactory that the system can reduce the air and fuel mixture. And injection of liquid using water vapor can reduce the level of CO and HC to the lowest level.